An Analysis of the Source and Nature of Technical Change: The Case of U.S. Agriculture - Chavas, Jean-Paul; Aliber, Michael; Cox, Thomas L. (The Review of Economics and Statistics, 1997)
This paper proposes a methodology to investigate the process of technical change with a focus on the dynamic effects of R&D investments on productivity, and on the induced innovation hypothesis for both inputs and outputs. The approach builds on a nonparametric representation of the underlying technology. An application to U.S. agriculture is presented. By distinguishing between private and public R&D investments, the analysis provides useful insights into the source and the dynamic nature of technical progress.